Collagen fiber reorganization in the rat ventral prostate following androgen deprivation: A possible role for smooth muscle cells - Vilamaior, Patrcia S. L.; Felisbino, Srgio L.; Taboga, Sebastio R. [UNESP]; Carvalho, Hernandes F. (Wiley, 2000)
BACKGROUND. Stroma plays an essential role in glandular function in different systems. In the prostate, it is responsible for the development and maintenance of the differentiated state of the epithelium. The marked reduction in the epithelial compartment of the prostate gland following castration is followed by a similarly important reorganization of the stroma. In this work, we characterized the reorganization of collagen fibers in the ventral prostate of castrated rats. METHODS. Histochemical tests and immunohistochemistry for type I and III collagens plus confocal microscopy of triple-labeled (collagen III, actin, and DNA) tissue sections were employed. RESULTS. We showed that collagen fibers are composed of type I and type III collagens and that they are progressively concentrated around the epithelial structures (ducts and acini) and become increasingly undulated and folded. Double-labeling of collagen fibers and F-actin demonstrated that smooth muscle cells (SMC) are intimately associated with collagen fibers. CONCLUSIONS. The results demonstrated a marked reorganization of the collagen fibers, and suggest an active role of the SMC in the reorganization of the fibrillar components of the stroma. (C) 2000 Wiley-Liss, Inc.
Keywords: Castration; Histochemistry; Polarizing microscope; Remodelling; Stroma; androgen; collagen fiber; collagen type 1; collagen type 2; F actin; animal experiment; animal tissue; castration; confocal microscopy; controlled study; epithelium; histochemistry; immunohistochemistry; priority journal; prostate ventral lobe; smooth muscle fiber; stroma; Cell Differentiation; Collagen; Immunohistochemistry; Muscle, Smooth; Prostate; Rats, Wistar